Rule of Law in Higher Education and University Institutions in Democratic Republic of the Congo: The Law of the Strongest or the Force of the Law (Case of the University of Gbado-Lite, North Ubangi Province) - Modeste Ndaba Modeawi; Ruphin Djolu Djoza; John Likolo Baya; Athené Kamondo Bisimuana; Koto-Te-Nyiwa Ngbolua (Britain International for Academic Research (BIAR-Publisher), 2022)
The crisis in which the Higher Education and University Sector is mired threatens the future of the nation; it is therefore necessary to put things in order. In a context where ignorance and non-respect of academic, regulatory and legal norms are manifest, where the attitude of managers in the conduct of academic affairs is subject to doubts and sometimes challenges, even questioning their profile as managers, The Vade Mecum as a reference document or guide for managers of higher education and university establishments (both public and private) is timely in indicating to the managers of establishments the line of conduct to follow in order to respect and ensure respect for the various texts and laws conceived, elaborated and published within the framework of higher education and university in the Democratic Republic of Congo. This study on the rule of law in the Higher Education and University Establishments in DR Congo is therefore an analysis of the realities observed in the administrative management of the scientific, administrative, technical and working personnel recruited, appointed and assigned in these Establishments who, it is believed, only have duties to fulfill while they also have rights to preserve and to assert. The case under examination is that of an Assistant of the University of Gbado-Lite (UNIGBA), recruited and appointed regularly by a decision of the Rector whose dismissal by the Head of School has seriously violated the legal and regulatory provisions on disciplinary procedure; the latter having introduced a hierarchical appeal, was rehabilitated in his functions and in his rights without other forms of trial.